The Effect of Self Efficacy and Information Quality on Behavioral Intention with Perceived Usefulness as Intervening Variable - Muslichah Muslichah (Journal of Accounting, Business and Management (JABM), 2018)
The rapid development of technology requires universities to develop an integrated academic information system to support the education process. With the application of the information system, universities can provide better information services to students. The aim of this study is to examine the influence of self-efficacy and information quality on behavioral intention toward academic information system with perceived usefulness as an intervening variable. This study used survey questionnaire in collecting data from one higher institution - STIE Malangkuçeçwara(Malangkuçeçwara School of Economic). The population in this study is all students in the sixth semester. A questionnaire was administered to all 377 students, 311 were returned yielding a response rate 82.5%. This study has three significant findings. First, the direct effect of self-efficacy on behavioral intention to use academic information system (AIS) is significant. Second, the direct effect of information quality on behavioral intention to use AIS is significant. Third, The indirect effect of self-efficacy and information quality on behavioral intention to use AIS through perceived usefulness is not significant